Strategi Australia dalam Menjaga Stabilitas Keamanan dan Menghadapi Persaingan Geopolitik di Kawasan Oceania - Ananda, Keisha; Olivia Dwi Salsabila; Alifa Rahmadani Nuzulia; Aisyah Permanda (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
This study examines Australia's strategy for maintaining security stability in Oceania amidst increasing non-traditional threats and global geopolitical competition. Oceania holds a strategic position in the Indo-Pacific region, serving as a key international trade route and a crucial location for the political and security interests of major powers. Island nations in the region face various challenges such as climate change, transnational crime, illegal fishing, and limited defense capacity. This study employed qualitative methods with desk research techniques and analyzed using the Regional Security Complex Theory. The results show that Australia carries out its role through military cooperation, development assistance, regional diplomacy, and human security programs focused on the well-being of Pacific communities. Australia is also actively strengthening relationships through regional forums such as the Pacific Islands Forum and the security stabilization mission in the Solomon Islands. This study finds that the influence of China and the United States has further complicated geopolitical competition in Oceania, requiring Australia to maintain a balance between security and economic interests. This study concludes that Australia remains a key actor in maintaining regional security stability, but the effectiveness of its role is influenced by the limited capacity of Pacific nations, global geopolitical pressures, and criticism of Australia's perceived over-dominant policies.